Probiotic potential of bacterial isolates from Klawalu Mangrove: Physiological characterization - Sukmawati, Sukmawati; Hardianti, Fatimah; Zakariah, Mohd Ihwan Bin; Sulfiana, Sulfiana; Riskawati, Riskawati (Biological Environment and Pollution, 2024)
Probiotic bacteria are a form of biological control because they play a role in suppressing or killing pathogenic microorganisms. Probiotic bacteria are capable of producing antimicrobial compounds such as lactic acid, hydrogen peroxide, and bacteriocins. The aim of this research is to determine the physiology of candidate probiotic bacteria, including their antimicrobial activity, resistance to acidic conditions, and resistance to bile salts. The research method is descriptive. The results of this study indicate that Bacillus safensis strain C251 SA3, Bacillus amyloliquefaciens strain NO10 SA8, and Bacillus australimaris strain IIHR GAPB01 SL1 are each capable of inhibiting the growth of pathogenic bacteria and surviving in acidic conditions (pH 2). However, only Bacillus amyloliquefaciens strain NO10 SA8 is resistant to bile salt pressure. Thus, the potential candidate for probiotic bacteria is Bacillus amyloliquefaciens strain NO10 SA8.